The economics of industrial cyberespionage - Stupak, O (2022)
Industrial cyberespionage is a widespread phenomenon that costs the global economy up to $6 trillion annually. It influences how we invest in innovation, store data, and create laws, and ultimately the welfare of society. Yet, it has received limited attention from the economics community. This thesis contributes to the emerging interdisciplinary field of economics of information security, bringing an economic perspective to the matter and considering industrial cyberespionage from three different angles.